Manejo Productivo de Pollos Camperos Aplicando Saberes Ancestrales - Tipantuña Mendoza, Paola Alexandra (2018)
This research was carried out at Universidad Tecnica de Cotopaxi in the experimental shed of the Veterinary Medicine major where the productive management of chickens was evaluated applying ancestral knowledge. In order to do this research the chickens were fed with corn and alfalfa and in the drinking water was added ancestral foods (onion (Allium cepa), garlic (Allium sativum) and chili pepper (Capsicum annuum), 80 day-old chickens were used, with an average weight of 30.12 g at arrival, which were randomly distributed in the different treatments, to the T1 was added 1 g / l of (Allium cepa) powder, T2 was added 1 g / l of (Allium sativum) powder, T3 was added 1 g / l of (Capsicum annuum) powder, and in T4 1.5 g / l of the mixture of (Allium cepa), (Allium sativum) and (Capsicum annuum) powder were added and to the control treatment T0 only simple water was provided, 4 repetitions were performed (4 chickens) by treatment (16 chickens) which were distributed under a completely randomized design (DCA), evaluating different parameters during the 52 days of research. The experimental results were processed in Infostat and Excel, which were subjected to an analysis of variance (ADEVA) and Fisher's test for the separation of means with a significance of P <0.05. It was determined that with the addition of chili pepper (Capsicum annuum) powder in the drinking water, the results obtained were higher when compared with the different treatments, as the chickens had a final weight of 1357.9 g, weight gain of 371 , 5 and a nutritional conversion of 1.34, stressing that 0% mortality was handled in the investigation. Similarly, through the economic analysis carried out through the Benefit / Cost indicator and taking into account the standing weight, it was determined that the highest profitability was obtained with the T3 to which chili was added (Capsicum annuum) in the drinking water with a benefit of $ 1.20 per bird and with the T0 which represented the same benefit because it was not spent on any ancestral food.